If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -1u = 7 Solving 20 + -1u = 7 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -1u = 7 + -20 Combine like terms: 20 + -20 = 0 0 + -1u = 7 + -20 -1u = 7 + -20 Combine like terms: 7 + -20 = -13 -1u = -13 Divide each side by '-1'. u = 13 Simplifying u = 13
| 42p=4-2p+8 | | x-2=14-6x+3 | | 16xf=176 | | 18a^2+46a-24=0 | | 5/2.1/2 | | 16-6a=-5-3a | | 5/2/12 | | (4x-1)(1+4x)= | | x+(x*.15)=400 | | 5-3(x-5)=13 | | ((4x^2-10x-2)/(2x-3)) | | (4x^2-10x-2)/(2x-3) | | -(1+5x)+8=-17+2x | | (ln*4x^2)-(ln*2x)=5 | | Y=-.5x+1.5 | | 14a^3b^2/21a^4b^3 | | b^4-8b+16=0 | | 5x/3-x=x/15-9/15 | | 3x+33=2x+156 | | (1/6r)/((r-7)/(56r^2-8r^3)) | | (2x^2y+2y+5)dx+(2x^3+2x)dy=0 | | 7x-10=-4(3-2x) | | 49x^2-b^2=0 | | (3x+y)(4x-y)= | | 19=m+5 | | 3x+21=12 | | (3x-y)(4x-y)= | | 4a+9=8a-18 | | 1x1/2 | | X(2x-1)(x-3)=o | | 5x+13=7x-11 | | -x-9-6x=-58 |